Buddhist-Christian Double Belonging in Resisting Ultranationalist Populism: The Case of Seiichi Yagi - Terasawa, Kunihiko (Buddhist Christian studies, 2026)
This article explores Seiichi Yagi's threefold framework - Front Structure, Field of Integration, and Field of Creative Emptiness - as a foundation for Buddhist-Christian dialogue and resistance to ultranationalist populism. Yagi's concept of "creative emptiness," integrating Buddhist śūnyatā and Christian kenosis, provides a metaphysical and practical vision for relational healing and transnational cooperation. The paper applies Yagi's thought to contemporary crises of ultranationalism and calls for a multidimensional dialogue - of head, heart, and hands - rooted in double belonging and embodied compassion.